Is Symptomatic Long QT Syndrome Associated with Depression in Women and Men?. Issue 3 (23rd August 2016) - Wesołowska, Karolina; Elovainio, Marko; Koponen, Mikael; Tuiskula, Annukka M.; Hintsanen, Mirka; Keltikangas‐Järvinen, Liisa; Määttänen, Ilmari; Swan, Heikki; Hintsa, Taina
Abstract: We examined whether long QT syndrome (LQTS) mutation carrier status or symptomatic LQTS are associated with depression, and whether there are sex differences in these potential relationships. The sample comprised 782 participants (252 men). Of the 369 genetically defined LQTS mutation carriers, 169 were symptomatic and 200 were asymptomatic. The control group consisted of 413 unaffected relatives. Depression was assessed using the Beck Depression Inventory‐II (BDI‐II). No association was found for LQTS mutation carrier status with depression. The multinomial logistic regression showed that LQTS mutation carrier men with arrhythmic events scored higher on depression compared with the control group, even when adjusting for age, β‐blockers, antidepressants, and social support ( OR = 1.09, 95 % CI [1.02, 1.15], p = .007). The binary logistic regression comparing symptomatic and asymptomatic LQTS mutation carriers showed that symptomatic LQTS was associated with depression in men ( OR = 1.10, 95 % CI [1.03, 1.19], p = .009). The results were unchanged when additionally adjusted for education. These findings suggest that symptomatic LQTS is associated with depression in men but not in women. Overall, however, depression is more frequent in women than men. Thus, regular screening for depression in LQTS mutation carriers and their unaffected family members can be important.